Toxic cadmium removal from water effluents by Rhizobium sp. (BJVr-12) extracellular polysaccaharides (EPS) - Paner, Estella T. (Journal of Environmental Science and Management, 1999)
Cadmium is one of the "big three" toxic metals (mercury, lead, and cadmium) well recognized for their deleterious effects on the environment. The capacity of coconut husk-immobilized Rhizobium sp. (BJVr-12) cells to adsorb Cd sup 2+ from aqueous solutions was studied. A maximum of 98.7 percent removal of Cd sup 2+ or 0.3 mg. Cd sup 2+/g cells was observed after two hours of elution at a flow rate of one milliliter per minute. The optimum flow rate for adsorption was determined by passing a solution containing 30 ppm Cd sup 2+ ions through the column at different flow rates. The slower flow rate (1 ml/min) gave the highest adsorption. The biosorption of Cd sup 2+ generally follows the Langmuir model of adsorption at low metal concentrations. The Langmuir constants for immobilized cells (EPS) in coconut husk are: Qo=0.04 mMCd (II)/g biomass; b = 19.42 m/M Cd (II)/g. The Freundlich constants are K = 0.7221 mM Cd (II)/g biomass; n =-1.4296/g biomass/L, while those for the coconut husk alone are Qo=0.0023 mM Cd sup 2+/g biomass b = -942.64 m/M Cd sup 2+/g and K = 0.2916 mMCd sup 2+/g biomass and n=18.027/g biomass/L. High values for Qo and K suggest many available binding sites for Cd sup 2+ on the bacterial surface. High values for b and n suggest high K affinity of the biomass for Cd sup 2+. Recovery of the biosorbed Cd from the biotraps using hydrochloric acid (6 M HCl) and citric acid (0.3 mM) was also studied. Results showed that HCl desorbed 0.3396 mg Cd (II) per 30 ml (72 percent Cd sup 2+ desorption) compared to citric acid which only desorbed 0.0833 mg Cd (II) per 30 ml (25 percent Cd sup 2+ desorption)